Healthy as a Horse? Characterising the UK and Ireland’s Horse Owners, Their Horses, and Owner-Reported Health and Behavioural Issues - Wendy Leah Watson; Jill R. D. MacKay; Cathy M. Dwyer (Animals)
This study focuses on recreational horse owners in the UK and Ireland to explore the relationship between horse characteristics and welfare issues. An online questionnaire was distributed to 1501 horse owners to collect data on the owners, horses, and health/behavioural issues. Most respondents were female (98%), lived in England (56%), and did not insure their horses for veterinary costs (51%). Horses were typically over 5 years of age (96%), taller than 154 cm (55%), and mostly geldings (65%). Common welfare issues reported included lameness (26%), handling problems (11%), antisocial behaviours (9%), and abnormal oral behaviours (9%). Older horses were 4.23 times more likely to have lameness issues than younger horses (95% CI [2.17, 9.27], p < 0.001), while sport horse breeds were 3.12 times more likely to exhibit abnormal oral behaviours (95% CI [2.10, 4.73], p < 0.001) compared to other breed types. Whilst the study found a relatively low rate of welfare issues, the main problems reported were consistent with those seen in other studies. Age and breed appeared to influence the prevalence of these issues, although the relationships were weak. The study suggests that factors such as the owner’s attitudes, knowledge, and management practices may play a significant role in the incidence of welfare problems. Further research is needed to explore the impact of management on horse welfare.